2009
DOI: 10.1158/1078-0432.ccr-08-1608
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PD-L1 Significantly Associates with Tumor Aggressiveness and Postoperative Recurrence in Human Hepatocellular Carcinoma

Abstract: Purpose: The aberrant expression of programmed cell death 1ligands 1and 2 (PD-Ls) on tumor cells dampens antitumor immunity, resulting in tumor immune evasion. In this study, we investigated the expression of PD-Ls in human hepatocellular carcinoma (HCC) to define their prognostic significance after curative surgery. Experimental Design: Immunohistochemistry was used to investigate PD-Ls expression as well as granzyme B + cytotoxic and FoxP3 + regulatory T cell infiltration on tissue microarrays containing 240… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
536
6
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 741 publications
(574 citation statements)
references
References 48 publications
27
536
6
5
Order By: Relevance
“…Our findings are different from the previous reports that B7-H1 expression is upregulated in many kinds of tumors and predicts a poor clinical outcome. [20][21][22][23] Although we were unable to obtain both parafinned and frozen specimens from the same patients and examine PD-1 and its ligands in the same tissue samples, we found that B7-H1 was expressed generally in nasopharyngeal carcinoma and control tissue, and either EpCAM þ epithelial tumor cells or EpCAM À stromal cells are the source of this PD-1 ligand. B7-H1 expression in the noncancerous control tissues is consistent with a previous report that B7-H1 is induced in infected or inflamed nasal tissue.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our findings are different from the previous reports that B7-H1 expression is upregulated in many kinds of tumors and predicts a poor clinical outcome. [20][21][22][23] Although we were unable to obtain both parafinned and frozen specimens from the same patients and examine PD-1 and its ligands in the same tissue samples, we found that B7-H1 was expressed generally in nasopharyngeal carcinoma and control tissue, and either EpCAM þ epithelial tumor cells or EpCAM À stromal cells are the source of this PD-1 ligand. B7-H1 expression in the noncancerous control tissues is consistent with a previous report that B7-H1 is induced in infected or inflamed nasal tissue.…”
Section: Discussionmentioning
confidence: 87%
“…[20][21][22][23] Therefore, we also used immunofluorescence co-staining of individual PD-1 ligands (B7-H1 and B7-DC) and an epithelial marker EpCAM to check the cell types expressing the ligands in the tumor and control tissue. As staining antibodies for these markers were only suitable for frozen sections, we used tissue sections of snapfrozen specimens from a separate group of patients.…”
Section: Pd-1 Ligand Expression In Nasopharyngeal Carcinoma and Contrmentioning
confidence: 99%
“…13,18 This technique may have a renew interests in light of the expression of programmed cell death 1 (PD1) pathway in HCC and recent encouraging outcome demonstrated in patients treated with Nivolumab. 19,20 An international registry of clinical trials on CIK was established in 2010 by SchmidtWolf et al, with an aim to collect clinical data and standardize treatment of patients with cancer using CIK cells. 21 In previously published studies, CIK treatment has been shown to significantly improve patient survival, especially when combined with minimally invasive treatments to give a synergistic effect.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 PD-L1 is expressed at high levels in several different cancers, 29 and the high levels of expression of PD-L1 on tumors is strongly associated with poor prognosis. 30,31 A recent study showed that the blockade of PD-1--PD-L signaling restored functional T-cell responses in several cancers and, subsequently, improved clinical outcomes. 32--34 In this study, the antitumor effects of the combination of IFN-atransfected tumor cell vaccine therapy and PD-1 blockade were evaluated in a poorly immunogenic murine colorectal cancer system as a preliminary investigation of the combined therapy before clinical studies.…”
Section: Introductionmentioning
confidence: 99%